Teacher Perceptions of the Merdeka Curriculum in English Teaching in Rural Elementary Schools - Nety, Nety; Widyastuti, Sri Harti; Santoso, Imam; Baharuddin, Baharuddin (UIR Press, 2026)
The continuous shifts in Indonesia’s educational curriculum have raised significant concerns about the effectiveness of English language teaching at the elementary school (ES) level, particularly in rural areas. While the Merdeka Curriculum (MC) emphasizes early language acquisition, its implementation faces challenges due to gaps in teacher preparedness, limited resources, and disparities between urban and rural schools. This study explores English teachers’ perceptions of the MC and the challenges they encounter in its implementation in rural elementary schools. This research uses a qualitative descriptive approach, with data collected through semi-structured interviews, observations, and document analysis from eight English teachers in five ES in Baubau, Southeast Sulawesi, Indonesia. Data analysis involved data condensation, display, and conclusion drawing. The findings show that while teachers recognize the potential of the MC, their understanding remains superficial, primarily acknowledging it as a new policy. The challenges identified include a lack of professional development opportunities, inadequate resources, and insufficient facilities, hindering the curriculum’s effective application. Teachers often rely on internet-based resources that are not tailored to local contexts and struggle with the student-centered, differentiated learning approach promoted by the curriculum. The study suggests that successful implementation of the MC requires support at both the central and local levels, including teacher training, infrastructure improvements, and appropriate resources. Further research should explore strategies to enhance teacher competencies and address infrastructural barriers, ensuring the full potential of the MC in rural education settings.